Tourism experiences and the lower risk of mortality in the Chinese elderly: a national cohort study - Min Du; Liyuan Tao; Min Liu; Jue Liu (BMC, 2021)
Abstract Background Cohort studies about the effects of tourism experiences on the risk of death among Chinese older adults are still lacking. We aimed to examine the association between tourism experiences and mortality in Chinese aged 65 or above. Methods We included 9520 participants aged 65 years or above from the Chinese Longitudinal Healthy Longevity Survey at baseline in 23 provinces in 2011. They were followed up in 2014 and 2018. Cox proportional hazards models were used to assess the association between tourism experiences and the risk of death. Results Among 9520 participants, 7.85% had at least one tourism experience outside of their local city/county during the past 2 years. During 35,994.26 person-years of follow-up, in total 4635 deaths were observed. The crude rate of death was greater in participants who had no tourism experience than in older travelers (incidence rate: 13.70 versus 5.24 per 100 person-years). Elderly travelers had a significantly lower risk for all-cause mortality (crude hazard ratio: 0.38, 95% CI: 0.33-0.44) compared with non-travelers. After adjustment for all covariates, the risk of all-cause mortality was 27% lower among those with at least one tourism experience than among non-travelers (adjusted hazard ratio: 0.73, 95% CI: 0.62-0.85). Subgroup analysis showed that the associations between tourism and the decreased risk of mortality were stable. Conclusions Tourism decreases the risk of mortality in the Chinese elderly. Tourism should be considered as a modifiable lifestyle factor and an effective way to reduce mortality and promote longevity and healthy aging.